First insights into the archaeometric analysis of the Los Amores Mosaic in Cástulo (Linares, Spain): the Judgement of Paris - Sánchez, Alberto (2021)
This paper discusses results obtained from in situ analysis of the tesserae of the Roman mosaic of Los Amores (Cástulo site, Linares, Spain) dating back to the turn of the 1st to the 2nd century AD. Specifically, it focuses on the scene The Judgment of Paris. In view of the exceptional state of preservation of the mosaic, from which very few tesserae had fallen off, non-invasive methods with portable Micro Raman Spectroscopy (MRS) and hand-held X-ray fluorescence (hXRF) and data assessment by use of principal component analysis and binary representations were selected. The results obtained allow to evaluate both the analytical method and the portable equipment used, as well as to classify the raw materials, the colouring agents and the opacifiers used. MRS analysis proved crucial for the identification of stone tesserae (ironstones, carbonate and siliciclastic rocks) and for the identification of the type of glasses used (soda-lime-silicate and lead type glasses) based on the analysis of two detached tesserae. hXRF analysis of the glass tesserae identified both colouring agents (Co, Cu, Pb, Zn) and opacifiers (calcium antimonate). The data obtained lend themselves to an assessment of the degradation process that threaten the integrity of the mosaic. The identification of tessera made of specific stone materials (especially ironstone) and of lead glass tesserae suggest the existence of a mosaic workshop in the Upper Guadalquivir (Eastern Andalusia, Spain).